Milestones in the History of Urban Development and the Compositional Reception of the City of Samarkand (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article reveals the historical and urban planning features of the formation of the ancient city of Samarkand.  The main points of the urban history of the creation of Samarkand in the XVII century are analyzed. Based on the data of written, archaeological and archival materials, the reconstruction of the plan of the central part of Samarkand of the XVII century was carried out. The stages of urban development of ancient Samarkand are traced.